Deciding When Hate Is a Crime: The First Amendment, Police Detectives, and the Identification of Hate Crime - Bell, Jeannine (2002)
This Article adds to the debate a story of how hate crime law is enforced, based on the experiences of the police detectives who are required to enforce hate crime law. Part I of this Article provides a brief description of hate crime laws and argues that the police play an important role in the determination of how hate crime law is enforced and ultimately, whether defendants’ First Amendment rights will be respected. Part II describes critics’ concerns about defendants’ First Amendment rights and the narrow constitutional line that enforcers of hate crime law must walk between enforcing hate crime and policing free speech. In Part III, I describe how enforcers decide that incidents are hate crimes and argue that they are able to avoid the pitfalls identified by critics. The Article concludes in Part IV with a discussion of the disconnect between hate crimes and hate speech and an exploration of new justifications for hate crime law